Multiculturalism Under Confinement: Prisoner Race Relations Inside Western Canadian Prisons. (June 2020) - Tetrault, Justin EC; Bucerius, Sandra M; Haggerty, Kevin D
What do race relations among Canadian prisoners tell us about national mythology, liberal multiculturalism, and racial colour-blindness? Drawing from almost 500 semi-structured interviews conducted with male prisoners inside four provincial institutions in Western Canada as part of the University of Alberta Prison Project, we analyse prisoners' perceptions of race and detail how their beliefs in Canada's national mythology – particularly multiculturalism – foster racial colour-blindness in daily prison life. Our data speak to both support for, and critiques of, liberal multiculturalism as a lived political philosophy. For instance, racial colour-blindness helps reduce ethnic conflict and encourages inter-group relations among racially diverse prisoners. As critics of liberal multiculturalism suggest, however, our participants individualized racism, focusing on what is often called 'overt racism' (such as white supremacy). Few participants acknowledged 'structural racism' or dwelled on the overrepresentation of people of colour in the prison system (even when housed on a unit that could contain over 60 per cent Indigenous prisoners). Some prisoners expressed a belief that Canada had overcome racism.